Differences in uni-dimensional breathlessness measures and thresholds for clinical response in a randomised controlled trial in people with chronic breathlessness: an exploratory study - David Currow; Magnus Ekström; Miriam Johnson; Sandra Louw; Philip McCloud; Katherine Clark; Diana Ferreira (BMJ Open Respiratory Research)
Introduction Optimally measuring improvements in chronic breathlessness in clinical practice and research continues to evolve. The aim of this study was to consider the performance of uni-dimensional measures in chronic breathlessness limiting exertion.Methods We report five measures of breathlessness (intensity: worst, best and average in the previous 24 hours; breathlessness now; and an affective component unpleasantness now) and two clinical thresholds over baseline on their 0–100 mm visual analogue scale (8.9 mm absolute improvement; and 15% relative improvement) collected in a multi-site, randomised, double-blind, parallel-arm, placebo-controlled trial of regular, low-dose, sustained-release morphine for people with chronic breathlessness with optimally treated underlying causes.Results Participants (n=284) were mostly elderly men with severe, chronic breathlessness. Worst breathlessness in the previous 24 hours showed improvement in people with more severe breathlessness and chronic obstructive pulmonary disease. By contrast, breathlessness now and average breathlessness in the previous 24 hours generated similar patterns of response, as did unpleasantness now and breathlessness now. Best breathlessness added little value. The two clinical thresholds showed differing patterns of significance.Discussion Consistent with other recent work, worst breathlessness may be an important uni-dimensional outcome in evaluating chronic breathlessness clinically and in research. This study does not support a differential between unpleasantness now and breathlessness now, previously observed in laboratory-generated, acute-on-chronic breathlessness. Timeframe for recall (now or the last 24 hours) and the threshold for a clinical meaningful improvement (absolute (8.9 mm) or relative (15%)) affect assessment performance.